2023
DOI: 10.1155/2023/5275439
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Stability Studies and Applications of Ti3C2Tx MXene

Abstract: The novel 2D materials, MXenes, have many remarkable properties, but their stability against oxidation is a major bottleneck in their applications. In this study, we have investigated the stability of Ti3C2Tx MXene for up to 365 days under different conditions, e.g., in liquid form in different solvents, in dried form when coated at polyethylene terephthalate (PET) substrate, and during the application of Ti3C2Tx MXene in polymer-dispersed liquid crystal- (PDLC-) based smart windows as conducting electrodes. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The observed spectral differences between the freshly formed films and those stored in oxygen may be attributed to the partial oxidation of MXene. Previous studies have shown that the extent of oxidation depends on the oxygen content during storage ,, and temperature …”
Section: Resultsmentioning
confidence: 99%
“…The observed spectral differences between the freshly formed films and those stored in oxygen may be attributed to the partial oxidation of MXene. Previous studies have shown that the extent of oxidation depends on the oxygen content during storage ,, and temperature …”
Section: Resultsmentioning
confidence: 99%
“…In basic media, the presence of OH À ions accelerates the oxidation of MXenes, and at higher MXene dispersion concentrations, the oxidation rate decreases due to steric shielding effects among the MXene flakes. 70,117…”
Section: Effect Of Ph On Mxene Oxidationmentioning
confidence: 99%
“…Fresh Ti 3 C 2 T x dispersions undergo a gradual color shift to a translucent cloudy appearance as oxidation progresses. 79,117 The rate of this change is notably influenced by both pH and reaction temperature. 77 Under fixed conditions of 20 °C, an increase in pH slows the rate of change, indicating that acidic conditions accelerate the oxidation process.…”
Section: Factors Influencing Mxene Oxidationmentioning
confidence: 99%